Self-Help Groups, Savings and Social Capital : Evidence from a Field Experiment in Cambodia - Ban, Radu (World Bank, Washington, DC, 2015)
This paper studies how self-help groups—village-based organizations designed to encourage savings, household production and social cohesion among the poor—can promote economic and social capital. The paper uses survey data and a wide array of social capital measures to assess the impact of a pilot program that was randomly rolled out in rural villages in Cambodia. The study finds that the program encouraged savings and associations via self-help groups. However it did not improve social capital measured by household and network surveys and lab activities that gauge trust, trustworthiness and the willingness to contribute to public goods. The findings contradict recent work that has found significant positive impacts of such groups on social capital. This paper evaluates community-wide impacts while most previous studies focus on program participants. In addition, the empirical strategy is based on a broader array of social capital measures, including behavioral indicators, suggesting that finding impacts of such programs on social capital is sensitive to the measurement strategy.